“I'm supposed to be a helper”: Spiritual distress of abortion providers after the Dobbs decisionAJOG Global Reports at a Glance - Leah M Bode, BS; Komal A Kumar, MD; Josie C McQuillan, BS; Nicole P Scott, MD; Caitlin Bernard, MD, MSCI (AJOG Global Reports, 2025)
Background: The Dobbs v. Jackson Women's Health Organization decision has undoubtably affected the practice of abortion providers nationally. We hypothesized that Dobbs has also impacted the ways in which providers experience meaning and purpose through their work, which are elements of spirituality. Objective: We sought to describe the spectrum of spirituality of abortion providers and understand whether and how the Dobbs decision caused spiritual distress. Study Design: For this qualitative study, we conducted video interviews with 26 abortion providers from 17 states between November 2022 and February 2023. States were classified according to the Guttmacher Institute classifications from most restrictive to very protective as of December 2022. Interviews included questions such as, “Can you describe your own sense of spirituality or spiritual identity?” and “How does your spiritual belief inform your response to the Dobbs decision?” Results: Participants’ states of practice were well-distributed across the abortion restrictive-protective spectrum. The majority of participants were spiritual, while less than half identified as part of an organized religion. Many participants felt a spiritual call or obligation to provide abortion care and 46% described abortion as a spiritual act for provider and/or patient. Most participants experienced spiritual distress (74%), including those practicing in states across the restrictive-protective spectrum. Of note, 92% of participants described their spirituality as helpful in coping with the effects of the fall of Roe v. Wade. Sources of strength included advocacy, agency, legislative work, and community; over half specifically cited the abortion provider community. Conclusions: The Dobbs decision—and subsequent state-level abortion restrictions—impacts abortion providers by causing spiritual distress. While many abortion-restrictive laws are influenced by religious or spiritual beliefs, it is important to recognize that abortion providers are also spiritual individuals.